The Personality of Students Studying the Social Etiquette and Personality Development Course by Myers Briggs Type Indicators (MBTI) Theory - Tananchai, Anongnart (ASEAN Journal of Education, 2017)
This study aimed to 1) investigate the personality of students according to the Myers- Briggs Type Indicator (MBTI) personality classifications, and 2) compare the personality patterns of students classified by the entrance examination channels and domiciles. The subjects in this study comprised eighty-five students taking the social etiquette and personality development course in class A1, during the first academic semester of 2014. The psychological personality test, (MBTI) Myers-Briggs Type Indicator, was used as a research tool and was provided through the Human metrics Jung Typology Test™ Instrument website. The data analysis was conducted in terms of percentage and frequency of distributions. The findings revealed that twelve patterns of students’ personality were found from all sixteen patterns. These patterns were divided into seven revealed personality patterns consisting of ESFP, ESTP, ESTJ, ESFJ, ENFP, ENFJ and ENTJ, and five concealed personality patterns consisting of ISTJ, ISFJ, INFJ, INTJ and INFP. The most prevalent revealed personality was ESFJ, followed by ENFJ, while the most prevalent concealed personality was INFJ. With reference to a comparison between the personality traits and the entrance examination channels, the students who passed with the Admission were more than those who took the entrance examination. The equally represented revealed personality patterns were found in both groups. In relation to a comparison between the personality traits and the domicile, most students were from the northeastern region of Thailand. The revealed personality patterns were found in every region, except the southern and the eastern regions. In conclusion, the results of this study can be used for the students’ personal and social development in order that they can be the people with the right personality according to their profession.